Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia as well as preparation method and application of Co-based intermetallic compound / carbon composite material
By preparing Co-based intermetallic compound/carbon composite materials, the efficiency problem of nitrate conversion to ammonia is solved, and high-efficiency electrocatalytic nitrate reduction is achieved, with excellent catalytic activity and stability, and is suitable for large-scale production.
Patent Information
- Application Number
- CN202510980565.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-07-16
AI Technical Summary
The prior art is difficult to efficiently convert nitrate into ammonia at room temperature and pressure, and the random distribution of active sites in traditional solid solution alloys limits the optimal distribution of NO3-/H+ on the catalyst surface, resulting in insufficient NO3RR activity.
Co-based intermetallic compound/carbon composite material is prepared by solid grinding method, a binary or ternary alloy is formed with specific metals and Co, and is loaded on a carbon support to form intermetallic compounds with long-range atomic order, and coordinate the regulation of NO3-adsorption and *H supply.
It realizes efficient electrocatalytic reduction of nitrate to ammonia at room temperature and pressure, has excellent catalytic activity and stability, and is suitable for large-scale mass production.
Smart Images

Figure CN120465043A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intermetallic compounds and relates to a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia, and a preparation method and application thereof, in particular to binary and ternary Co-based intermetallic compound / carbon composite materials, preparation methods and applications in electrocatalytic synthesis of ammonia. Background Art
[0002] Groundwater is an important freshwater resource for humans. However, the nitrate content in groundwater has increased in recent years, which poses a threat to human health and reduces the quality of agricultural products. In addition, the demand for ammonia (NH3) in many fields such as fertilizer manufacturing and energy production is increasing, and the current industrial synthesis of NH3 mainly relies on the energy-intensive Haber-Bosch process. To solve these problems, the electrocatalytic nitrate reduction reaction (NO3RR) carried out at room temperature and pressure has attracted widespread attention. This reaction not only provides a way to sustainably control nitrate pollution in groundwater, but also promotes the preparation of renewable NH3. Previous studies have explored a variety of metal-based catalysts (such as Cu, Ru, Pd, Co, etc.) for NO3 - Selective conversion to NH3. Among them, Co-based materials are considered as potential catalysts for NO3RR due to their excellent NH3 selectivity, which is mainly attributed to their unfilled d orbital electrons, which can efficiently activate NO3 - However, the NO3RR mechanism involves a complex eight-electron / nine-proton transfer process that is highly dependent on active hydrogen (*H) from water dissociation and competes with the hydrogen evolution reaction (HER) at the catalyst-electrolyte interface. - Improved adsorption and increased *H supply synergistically achieve high NH3 selectivity and yield. However, balancing these two at active sites remains a key challenge for NO3RR.
[0003] To solve this problem, alloying catalytic metals with promoting elements has been widely studied, but the random distribution of active sites in traditional solid solution alloys limits the NO3 - / H + In contrast, intermetallic compounds (IMCs) with long-range atomic order can provide catalytic sites with uniform configuration, thus promoting NO3 - Synergistic optimization of adsorption and *H transfer. In addition, IMCs exhibit excellent structural and performance stability because their active site configuration can be precisely controlled by adjusting the stoichiometric ratio guided by the phase diagram, and the formed structure has a low formation enthalpy. Therefore, by combining catalytic metals with promoting elements to construct IMCs, it is a good opportunity to synergistically regulate NO3 - adsorption and *H supply, thereby enhancing NO3RR activity.
[0004] Therefore, it is of great significance to develop an intermetallic compound catalyst that can quickly and efficiently convert nitrate into ammonia. Summary of the Invention
[0005] In order to solve the current technical difficulties, the present invention provides a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia, as well as a preparation method and application thereof.
[0006] The technical solutions of the present invention are as follows: A Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia, comprising a Co-based intermetallic compound and a carbon support; the general formula of the Co-based intermetallic compound is Co x M y , wherein x is 1-7, y is 1-4; the metal M is one or two of metal germanium (Ge), tin (Sn), nickel (Ni), and copper (Cu); the Co-based intermetallic compound is uniformly loaded on a carbon support.
[0007] According to the present invention, preferably, the metal M is germanium (Ge), tin (Sn), a combination of germanium (Ge) and nickel (Ni), a combination of nickel (Ni) and tin (Sn), or a combination of germanium (Ge) and copper (Cu).
[0008] According to the present invention, the Co-based intermetallic compound for electrocatalytic synthesis of ammonia is preferably selected from one of the following compounds: Co2Ge, Co7Ge4, Co3Ge2, CoGe, Co 2.9 Sn2, CoNiGe, CoNiSn, Co2CuGe2.
[0009] According to the present invention, the method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis comprises the following steps: (1) uniformly mixing a metal Co precursor, a metal M precursor, monocyanamide, and a carbon support by a solid grinding method to obtain a mixture; (2) The mixture obtained in step (1) is subjected to high-temperature heat treatment in a reducing atmosphere to obtain a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia.
[0010] According to the preferred embodiment of the present invention, the metallic Co precursor in step (1) is a water-soluble Co salt, more preferably Co(NO3)2·6H2O.
[0011] According to the present invention, preferably, the metal M precursor in step (1) is a water-soluble metal M salt, and the metal M is one or two of metal germanium (Ge), tin (Sn), nickel (Ni), and copper (Cu); further preferably, the metal germanium precursor is (NH4)2GeF6, the metal tin precursor is SnCl2·2H2O, the metal nickel precursor is Ni(NO3)2·6H2O, and the metal copper precursor is Cu(NO3)2·3H2O.
[0012] According to the preferred embodiment of the present invention, the ratio of the mass of the cyanamide to the molar number of the metal Co precursor in step (1) is 50-150 mg:0.1 mmol.
[0013] According to the preferred embodiment of the present invention, the carbon carrier in step (1) is superconducting carbon Ketjen black, carbon nanotubes, carbon black (Vulcan xc-72R) or carbon nanofibers (CNFs); the ratio of the mass of the carbon carrier to the molar number of the metal Co precursor is 30-90 mg:0.1 mmol.
[0014] According to the preferred embodiment of the present invention, in step (1), the solid grinding step is: mixing the metal Co precursor, the metal M precursor and the monocyanamide, grinding for 5-15 minutes, and then adding the carbon support and continuing to grind for 20-30 minutes to obtain a mixture.
[0015] Preferably, according to the present invention, the reducing atmosphere in step (2) is an argon-hydrogen mixed gas, and the volume fraction of hydrogen in the mixed gas is 5-10%.
[0016] Preferably, according to the present invention, the temperature of the high-temperature heat treatment in step (2) is 700-1000°C, the time of the high-temperature heat treatment is 3-12h; and the heating rate of the high-temperature heat treatment process is 2-8°C / min.
[0017] The present invention also provides the use of the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis in electrocatalytic nitrate reduction to synthesize ammonia.
[0018] The technical features and beneficial effects of the present invention are as follows: 1. The target Co-based intermetallic compound prepared by the present invention through a simple solid grinding method is not only simple and quick to operate, but also easy to mass-produce. The metal Co precursor and other metal precursors are both abundant, cheap and readily available. In addition, the target Co-based intermetallic compound has the advantages of large specific surface area, excellent catalytic activity and excellent stability. It exhibits excellent catalytic activity and stability in the electrocatalytic nitrate reduction synthesis of ammonia, meets the requirements of application and development in related fields, and has good application prospects.
[0019] 2. In the preparation of the Co-based intermetallic compound of the present invention, a specific metal is selected to form a binary or ternary alloy with Co, and is loaded on a specific carrier, thereby ensuring that the resulting composite material has excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 X-ray diffraction patterns (XRD) of the Co-based intermetallic compound / carbon composite materials prepared in Examples 1-4, wherein (a) Co2Ge / C; (b) Co7Ge4 / C; (c) Co3Ge2 / C; and (d) CoGe / C.
[0021] Figure 2 The X-ray diffraction patterns (XRD) of the Co-based intermetallic compound / carbon composite material prepared in Examples 5-8, wherein (a) Co 2.9 Sn2 / C; (b) CoNiGe / C; (c) CoNiSn / C; (d) Co2CuGe2 / C.
[0022] Figure 3 Scanning electron microscope (SEM) images of the Co-based intermetallic compound / carbon composite materials prepared in Examples 1-4, wherein (a) Co2Ge / C; (b) Co7Ge4 / C; (c) Co3Ge2 / C; and (d) CoGe / C.
[0023] Figure 4 These are low-magnification high-angle dark field scanning transmission electron microscopy (HAADF-STEM) images of the Co-based intermetallic compound / carbon composite materials prepared in Examples 1-4, where (a) Co2Ge / C; (b) Co7Ge4 / C; (c) Co3Ge2 / C; and (d) CoGe / C.
[0024] Figure 5 The Co-based intermetallic compound / carbon composite material prepared in Example 1-4 was placed in a 0.1 mol / L KOH solution with or without 500 ppm NO3 - Linear sweep voltammetry (LSV) curves at -N, where (a) Co2Ge / C; (b) Co7Ge4 / C; (c) Co3Ge2 / C; (d) CoGe / C.
[0025] Figure 6 The Co-based intermetallic compound / carbon composite material prepared in Example 1-4 was dissolved in 0.1 mol / L KOH solution and 500 ppm NO3 - Ammonia yield and Faradaic efficiency (FE) at -N, where (a) Co2Ge / C; (b) Co7Ge4 / C; (c) Co3Ge2 / C; (d) CoGe / C.
[0026] Figure 7 The Co-based intermetallic compound / carbon composite material prepared in Example 9 was dissolved in 0.1 mol / L KOH solution and 500 ppm NO3 - -N ammonia yield and Faradaic efficiency (FE).
[0027] Figure 8 The Co-based intermetallic compound / carbon composite material prepared in Example 2 was dissolved in 0.1 mol / L KOH solution and 500 ppm NO3 - Ammonia yield and Faradaic efficiency (FE) after 15 cycles of stability experiment under -N.
[0028] Figure 9 The Co-based intermetallic compound / carbon composite material prepared in Example 2 was dissolved in 0.1 mol / L KOH solution and 500 ppm NO3 - X-ray diffraction (XRD) pattern of the sample after 15 cycles of stability test under -N.
[0029] Figure 10 The Co-based intermetallic compound / carbon composite material prepared in Example 2 was dissolved in 0.1 mol / L KOH solution and 500 ppm NO3 - Morphological characterization of the sample after 15 cycles of stability test under -N, including (a) scanning electron microscopy (SEM); (b) low-magnification transmission electron microscopy (TEM) image. DETAILED DESCRIPTION
[0030] To better understand the technical solutions of the present invention, the present invention includes but is not limited to the specific embodiments described below. Similar technologies and methods should be considered within the scope of protection of the present invention. To further clarify the technical problems, technical solutions, and advantages to be solved by the present invention, the following detailed description is provided in conjunction with the accompanying drawings and specific embodiments.
[0031] It should be understood that the embodiments described herein are only a portion of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0032] Example 1 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.2 mmol Co(NO3)2·6H2O, 0.1 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0033] 2) Preparation of Co2Ge intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with a hydrogen volume fraction of 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a Co2Ge intermetallic compound / carbon composite material, denoted as Co2Ge / C.
[0034] Example 2 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.175 mmol Co(NO3)2·6H2O, 0.1 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0035] 2) Preparation of Co7Ge4 intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with the volume fraction of hydrogen in the mixed gas being 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a Co7Ge4 intermetallic compound / carbon composite material, denoted as Co7Ge4 / C.
[0036] Example 3 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.15 mmol Co(NO3)2·6H2O, 0.1 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0037] 2) Preparation of Co3Ge2 intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with the volume fraction of hydrogen in the mixed gas being 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a Co3Ge2 intermetallic compound / carbon composite material, denoted as Co3Ge2 / C.
[0038] Example 4 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.1 mmol Co(NO3)2·6H2O, 0.1 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0039] 2) Preparation of CoGe intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with a hydrogen volume fraction of 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a CoGe intermetallic compound / carbon composite material, denoted as CoGe / C.
[0040] Example 5 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.12 mmol Co(NO3)2·6H2O and 0.08 mmol SnCl2·2H2O metal precursors and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0041] 2) Co 2.9 Preparation of Sn2 intermetallic compound / carbon composite material: The mixture was heated to 900℃ at a heating rate of 5℃ / min in a reducing atmosphere (argon-hydrogen mixed gas, with a volume fraction of hydrogen in the mixed gas of 5%), kept at this temperature for 3h, and naturally cooled to room temperature to obtain Co 2.9 Sn2 intermetallic compound / carbon composite material, denoted as Co 2.9 Sn2 / C.
[0042] Example 6 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.1 mmol Co(NO3)2·6H2O, 0.1 mmol Ni(NO3)2·6H2O, 0.1 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0043] 2) Preparation of CoNiGe intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with a hydrogen volume fraction of 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a CoNiGe intermetallic compound / carbon composite material, denoted as CoNiGe / C.
[0044] Example 7 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.1 mmol Co(NO3)2·6H2O, 0.1 mmol Ni(NO3)2·6H2O, and 0.1 mmol SnCl2·2H2O metal precursors and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0045] 2) Preparation of CoNiSn intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with a hydrogen volume fraction of 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a CoNiSn intermetallic compound / carbon composite material, denoted as CoNiSn / C.
[0046] Example 8 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia comprises the following steps: 1) Preparation of the mixture: Grind 0.2 mmol Co(NO3)2·6H2O, 0.1 mmol Cu(NO3)2·3H2O, 0.2 mmol (NH4)2GeF6 metal precursor, and 100 mg of monocyanamide in a mortar for 10 minutes, then add 64 mg of superconducting carbon Ketjen black and continue grinding for 20 minutes to fully mix and form a mixture.
[0047] 2) Preparation of Co2CuGe2 intermetallic compound / carbon composite material: The mixture was heated to 900°C at a heating rate of 5°C / min in a reducing atmosphere (argon-hydrogen mixed gas, with the volume fraction of hydrogen in the mixed gas being 5%), heat treated at this temperature for 6 hours, and naturally cooled to room temperature to obtain a Co2CuGe2 intermetallic compound / carbon composite material, denoted as Co2CuGe2 / C.
[0048] Example 9 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia is as described in Example 2, except that an equal mass of carbon nanotubes is used in step (1) instead of superconducting carbon Ketjen black.
[0049] Comparative Example 1 A method for preparing a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia is as described in Example 2, except that no carbon carrier is added.
[0050] In this comparative example, no carbon support was added, and a Co-based intermetallic compound could not be obtained.
[0051] The comprehensive analysis is as follows: 1. X-ray powder diffraction, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) The X-ray diffraction patterns (XRD) of the Co-based intermetallic compound / carbon composite materials prepared in Examples 1-8 are as follows: Figure 1-2 As shown by Figure 1-2 It can be seen that the X-ray diffraction pattern of the obtained product corresponds to the standard pattern of the corresponding Co-based intermetallic compound, and a characteristic peak of carbon appears at around 24°.
[0052] Figure 3-4 The SEM and TEM images of the Co-based intermetallic compound / carbon composite material prepared in Examples 1-4 are shown in FIG. Figure 3-4 It can be seen that the Co-based intermetallic compounds prepared in Examples 1-4 have a rough and porous structure, a large specific surface area, and the nanoparticles are evenly distributed on the superconducting carbon Ketjen black. The particle sizes of Co2Ge, Co7Ge4, Co3Ge2, and CoGe / C are approximately 27nm, 23nm, 24nm, and 22nm, respectively.
[0053] 2. Performance of Co-based intermetallic compounds in nitrate reduction (NO3RR) (1) The performance of the Co-based intermetallic compound / carbon composite material prepared in Examples 1-4 as a catalyst in nitrate reduction (NO3RR) was tested by linear sweep voltammetry. The specific steps are as follows: i. Preparation of working electrode: 5 mg of catalyst sample, 50 μL of 5 wt% Nafion solution and 950 μL of isopropanol were ultrasonically mixed for 1 hour to prepare a uniform black ink. Then 200 μL of catalyst ink was evenly coated on a 1 cm 2 On carbon paper (CP), air-dried, the working electrode was obtained, and the catalyst loading was 1 mg / cm 2 .
[0054] ii. The reduction reaction (NO3RR) performance was evaluated in a three-electrode system using a CHI 660E electrochemical workstation. The electrode obtained in step i was used as the working electrode, the counter electrode was a platinum electrode, the reference electrode was an Ag / AgCl electrode, and the electrolyte contained 500 ppm NO3 - -N (provided by KNO3) in a 0.1 mol / L KOH aqueous solution. The test was carried out in an H-type electrolytic cell. The anode and cathode compartments were separated by a Nafion 211 membrane. The membrane was pretreated as follows: first, it was immersed in a 5 wt% H2O2 aqueous solution at 50°C for 1 hour, then treated in a 0.1 mol / L H2SO4 aqueous solution at 50°C for 1 hour, and finally rinsed repeatedly with deionized water. All potentials were converted to the reversible hydrogen electrode (RHE) scale (E RHE =E Ag / AgC +0.059×pH+0.197V), the test potential range was 0 to -0.85 V (vs. RHE), and the scan rate was 10 mV s -1 In order to investigate the influence of nitrate ions, - The test was carried out under -N conditions, and all data were not IR corrected.
[0055] The results are as follows Figure 5 As shown by Figure 5 It can be seen that the current density of the Co-based intermetallic compound / carbon composite materials prepared in Examples 1-4 with nitrate is much greater than the current density without nitrate, indicating that all Co-based intermetallic compounds have catalytic performance for NO3RR.
[0056] (2) Different voltages were selected to test the ammonia yield and Faraday efficiency The specific test steps are as follows: Apply a working potential of -0.4V to -0.8V (vs. RHE) to the working electrode, perform chronoamperometry test and continue electrolysis for 1 hour, record the accumulated electricity during the electrolysis process. After the electrolysis is completed, the indigo blue colorimetric method is used to determine the NH4 + The ammonia yield and the corresponding Faradaic efficiency were calculated based on the absorbance.
[0057] The results are as follows Figure 6 As shown by Figure 6 It can be seen that the yield of ammonia increases with the increase of voltage. At -0.8 V, Co2Ge / C, Co7Ge4 / C, Co3Ge2 / C, and CoGe / C have the largest ammonia yields, which are 6.95 mg h -1 cm -2 、7.56mgh -1 cm -2 , 7.15mg h -1 cm -2, 5.79mg h -1 cm -2 However, the Faradaic efficiency of ammonia first increases and then decreases with increasing voltage, reaching a maximum value at -0.6V, which are 91.47%, 97.76%, 94.24% and 88.94% respectively, indicating that Co7Ge4 / C has the best NO3RR performance and this performance is better than most of the reported electrocatalysts. The ammonia yield and Faradaic efficiency of the Co-based intermetallic compound / carbon composite material obtained by replacing the carbon support with carbon nanotubes in Example 9 are as follows: Figure 7 As shown by Figure 7 It can be seen that the maximum ammonia yield is 7.04 mg h at -0.8 V. -1 cm -2 , the maximum Faraday efficiency is 93.02% at -0.6V, which is lower than the composite material obtained by superconducting carbon Ketjen black as the carbon carrier.
[0058] (3) Stability test Stability is another important indicator for evaluating the practical application of electrocatalysts, such as Figure 8 As shown in FIG, 15 cycles were conducted at -0.6 V, and it was found that the ammonia yield and the Faradaic efficiency remained almost unchanged, proving that the Co-based intermetallic compound / carbon composite material prepared in Example 2 has excellent stability. Subsequently, the electrolyzed sample was characterized by XRD, SEM and TEM, as shown in FIG. Figure 9 and Figure 10 As shown, it was found that its morphology and crystal phase did not change, further proving the excellent stability of Co7Ge4 intermetallic compounds.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0060] Furthermore, those skilled in the art will appreciate that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of the present invention and to form different embodiments. For example, in the claims above, any of the claimed embodiments may be used in any combination. The information disclosed in this background section is intended solely to enhance understanding of the overall background of the present invention and should not be construed as an admission or any form of implication that such information constitutes prior art known to those skilled in the art.
Claims
1. A Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia, characterized in that: It includes a Co-based intermetallic compound and a carbon support; the general formula of the Co-based intermetallic compound is Co x M y , wherein x is 1-7, y is 1-4; the metal M is one or two of metal germanium, tin, nickel, and copper; the Co-based intermetallic compound is uniformly loaded on a carbon support; the carbon support is superconducting carbon Ketjen black, carbon nanotubes, carbon black, or carbon nanofibers.
2. The Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 1, characterized in that: The metal M is germanium, tin, a combination of germanium and nickel, a combination of nickel and tin, or a combination of germanium and copper.
3. The Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 1, characterized in that: The Co-based intermetallic compound for electrocatalytic synthesis of ammonia is selected from one of the following compounds: Co2Ge, Co7Ge4, Co3Ge2, CoGe, Co 2.9 Sn2, CoNiGe, CoNiSn, Co2CuGe2.
4. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) uniformly mixing a metal Co precursor, a metal M precursor, monocyanamide, and a carbon support by a solid grinding method to obtain a mixture; (2) The mixture obtained in step (1) is subjected to high-temperature heat treatment in a reducing atmosphere to obtain a Co-based intermetallic compound / carbon composite material for electrocatalytic synthesis of ammonia.
5. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 4, characterized in that: In step (1), the metal Co precursor is a water-soluble Co salt; the metal M precursor is a water-soluble metal M salt, and the metal M is one or two of metal germanium, tin, nickel, and copper.
6. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 5, characterized in that: In step (1), the metal Co precursor is Co(NO3)2·6H2O; the metal germanium precursor is (NH4)2GeF6, the metal tin precursor is SnCl2·2H2O, the metal nickel precursor is Ni(NO3)2·6H2O, and the metal copper precursor is Cu(NO3)2·3H2O.
7. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 4, characterized in that: The ratio of the mass of the monocyanamide to the molar number of the metal Co precursor in step (1) is 50-150 mg:0.1 mmol; The carbon carrier is superconducting carbon Ketjen black, carbon nanotubes, carbon black or carbon nanofibers; the ratio of the mass of the carbon carrier to the molar number of the metal Co precursor is 30-90 mg:0.1 mmol.
8. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 4, characterized in that: In step (1), the solid grinding step is: mixing the metal Co precursor, the metal M precursor, and monocyanamide, grinding for 5-15 minutes, and then adding the carbon support and continuing to grind for 20-30 minutes to obtain a mixture.
9. The method for preparing the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to claim 4, characterized in that: The reducing atmosphere in step (2) is an argon-hydrogen mixed gas, and the volume fraction of hydrogen in the mixed gas is 5-10%; the temperature of the high-temperature heat treatment is 700-1000°C, and the time of the high-temperature heat treatment is 3-12h; the heating rate of the high-temperature heat treatment process is 2-8°C / min.
10. Use of the Co-based intermetallic compound / carbon composite material for electrocatalytic ammonia synthesis according to any one of claims 1 to 3 in electrocatalytic nitrate reduction to synthesize ammonia.
Citation Information
Patent Citations
CoNi / C nano composite material, preparation method thereof and application of CoNi / C nano composite material in electrocatalytic nitrogen fixation and ammonia synthesis
CN113755874A
CoFe alloy catalytic electrode material, preparation method and application
CN116103687A
Preparation method and application of Cu-Co-based electro-catalytic material
CN117926327A
Device and methods for production of ammonia and nitrates under ambient conditions
US20230340677A1